Tanggung Jawab Maskapai Penerbangan Sebagai Penyedia Jasa Penerbangan Kepada Penumpang Akibat Keterlambatan Penerbangan - Baiq Setiani (Jurnal Hukum Novelty, 2016)
ABSTRACTThe background of this research is the increasing frequency of passengers or users of air transport services in Indonesia who complained about the airline services, especially flight delays problems in the implementation of air transport services. Thus, it is important to reveal how the implementation of the airline responsibility as a flight services provider to the passengers in case of flight delays according to the legislation that applies. The method used is a normative juridical research. Based on this research, the form of airlines responsibilities applied the concept of legal presumption of innocence responsibility. The legal protection to passengers as a result of delays can be proven with air tickets. A suggestion in this study is the government should provide clear and assertive provisions on sanctions against the airlines if it does not provide compensation due to the delays.